PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN (Studi Pada Perusahaan Properti dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2015) - Ardi Wiranata; Andewi Rokhmawati; Yulia Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research was to know the influence of foreign ownership, managerial ownership, institutional ownership, capital structure, company size to company performance. The capital structure in this study is calculated through debt equity ratio (DER) and firm size was calculated with logarithma of total asset. While the bound variable in this research is measured by return on asset (ROA). This study was conducted on property and real estate companies listed on the Indonesian Stock Exchange (IDX) from 2011-2015. The samples studied were 36 companies obtained by purposive sampling method. The type of data used is secondary data obtained by using documentation method. Data analysis method used in this research was multiple linear regression. The simultaneous test results of ownership structure, capital structure, firm size have significant effect to company performance. Partial test of foreign ownership does not have on effect on company performance. Managerial ownership does not have on effect on company performance. Instutitional ownership has a significant effect on company performance. Capital structure has a significant effect on company performance. Company size has a significant effect on company performance.Keywords : Ownership Structure, Capital Structure, Company Size, Company Performance